The effect of dose-interval on antibody response to mRNA COVID-19 vaccines: a prospective cohort study - Almeida, Nisha D.; Schiller, Ian; Ke, Danbing; Sakr, Elsa; Plesa, Maria; Vanamala, Sandeep; Moneger, Anne-Laure; Bazan, Maria; Lucchesi, Chiara; Wozniak, Natalia; Fritz, Jorg H.; Piccirillo, Ciriaco A.; et al. (Frontiers in Immunology, 2024)
Vaccination against COVID-19 is highly effective in preventing severe disease and hospitalization, but primary COVID mRNA vaccination schedules often differed from those recommended by the manufacturers due to supply chain issues. We investigated the impact of delaying the second dose on antibody responses to COVID mRNA-vaccines in a prospective cohort of health-care workers in Quebec.We recruited participants from the McGill University Health Centre who provided serum or participant-collected dried blood samples (DBS) at 28-days, 3 months, and 6 months post-second dose and at 28-days after a third dose. IgG antibodies to SARS-CoV2 spike (S), the receptor-binding domain (RBD), nucleocapsid (N) and neutralizing antibodies to the ancestral strain were assessed by enzyme-linked immunosorbent assay (ELISA). We examined associations between long (>89 days) versus short (<89 days) between-dose intervals and antibody response through multivariate mixed-effects models adjusted for age, sex, prior covid infection status, time since vaccine dose, and assay batch.The cohort included 328 participants who received up to three vaccine doses (>80% Pfizer-BioNTech). Weighted averages of the serum (n=744) and DBS (n=216) cohort results from the multivariable models showed that IgG anti-S was 31% higher (95% CI: 12% to 53%) and IgG anti-RBD was 37% higher (95% CI: 14% to 65%) in the long vs. short interval participants, across all time points.Our study indicates that extending the covid primary series between-dose interval beyond 89 days (approximately 3 months) provides stronger antibody responses than intervals less than 89 days. Our demonstration of a more robust antibody response with a longer between dose interval is reassuring as logistical and supply challenges are navigated in low-resource settings.